New fossil lace bugs (Heteroptera: Tingidae) from the Middle Eocene of the Grube Messel (Germany), with a catalog of fossil lace bugs - Wappler, Torsten (Zootaxa, 2003)
Lace bugs (Heteroptera: Tingidae) comprise over 2.100 species classified in two subfamilies. So far, nearly 36 fossil species of Tingidae have been described, most of Cenozoic age. The present paper reports on three new species genera of Tingidae from the late Middle Eocene Grube Messel (Germany), inscribed on the UNESCO World Heritage List, describing Exmesselensis disspinosus gen. et sp. n. (Canatacaderinae: Phatnomini), Chorotingiotes prisca gen. et sp. n. (Tinginae: Ypsotingini), and Oblongomorpha lutetia gen. et sp. n. (Tinginae: Litadeini). The specimens from Messel show once more that Cantacaderinae, especially of the tribe Phatnomini were widespread and highly diverse in Europe during the Paleogene than today. Oblongomorpha n. gen. and Chorotingioites n. gen. demonstrate that even the differentiation of the Tinginae in the main tribes has taken place in this period or earlier. A taxonomic catalog of all described, fossil lace bugs is appended.